The Regulation of Contractual Liability of the State in Argentine Law - Perrino, Pablo Esteban (2015)
The author of this article details how we would state responsibility of the state in cases of error, for which develops the figure within the public sphere. In that sense, the deeper the scope and types of regulated responsibilities, according to the study carried out it comes. Subsequently, a detailed analysis of the contractual and extra-contractual responsibility of the state in various situations within the field of public management is done. Finally, assumptions configuration of different types of state responsibility develops.